The Influence And Effectiveness of Training on Workforce Performance Using The Kirkpatrick Evaluation Model of PT Pertamina Hulu Rokan - Amelia Rahmita Johar; Andriyastuti Suratman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
For workers, training, skills, information technology, knowledge, professional ethics are very important for the world of work. The KirkPatrick Evaluation Model attempts to help analyze whether existing training in a company is running effectively. So from this paper, it can be concluded that the training carried out by the company has received a very positive response from the workers so that the results of the evaluation that has been carried out are useful for the company and subsequent training.